Perceived Fairness in English Language Assessment: Insights from EFL Students and Teachers - Supartini, Ni Luh; Benu, Naniana; Mahendra, Wayan Eka (Journal of Languages and Language Teaching, 2025)
This paper examines perceptions of fairness in English language assessment from both students’ and teachers’ perspectives through a descriptive literature review of five recent peer-reviewed studies. The review followed Snyder’s (2019) framework for literature reviews, encompassing the design, selection, analysis, and synthesis phases. Studies were selected based on their focus on fairness in the classroom and large-scale assessments, representation of both student and teacher perspectives, and publication within the last five years in reputable journals. The analysis synthesized findings across dimensions of distributive, procedural, and interactional fairness, as well as the influence of cultural and institutional contexts. The review reveals that students often value traditional assessment methods for their perceived learning support, yet express concerns about bias, transparency, and cultural relevance. Teachers, while generally aware of fairness principles, display variations in assessment literacy and implementation depending on training, experience, and organizational structures. The findings underscore the importance of strengthening Language Assessment Literacy (LAL), promoting culturally responsive assessment practices, and fostering Professional Learning Communities (PLCs) to bridge gaps between teacher and student perceptions. These insights carry practical implications for teacher education, institutional policy, and the design of fairer and more inclusive English language assessments.